Effects of Sevoflurane on Hemodynamics and Inducible Nitric Oxide Synthase/Soluble Guanylate Cyclase Signaling Pathway in a Rat Model of Pulmonary Arterial Hypertension. (July 2017) - Qin, Gang; Luo, Hui; Yin, Xiaoqing; Wang, Lu; Zhang, Junjie; Cao, Yanan; Zhang, Zhong; Ye, Zhi; Wang, E.
Abstract : BACKGROUND: The effects of sevoflurane on right ventricular (RV) function are incompletely understood. In a rat model of experimentally induced pulmonary arterial hypertension (PAH), we studied effects of sevoflurane on RV function and the expression of inducible nitric oxide synthase/soluble guanylate cyclase (iNOS/sGC) signaling pathway. We hypothesized that sevoflurane would improve RV function in rats with PAH via a iNOS/sGC pathway. METHODS: To induce PAH, Sprague-Dawley rats were randomly assigned to treatment with monocrotaline or normal saline. Four weeks later, rats were then randomly assigned to either control or sevoflurane inhalation. After rats were anesthetized and instrumented with a pulmonary artery or RV conductance catheter, they were treated with inhaled sevoflurane at 3 doses for 90 minutes each. Hemodynamic changes and expression of iNOS and sGC were recorded. RESULTS: Sevoflurane inhalation depressed RV function in both normal and PAH rats. However, RV dP/dtmax fell to a lesser degree in rats with PAH than normal rats. Sevoflurane inhalation increased iNOS expression, but decreased sGC expression. CONCLUSIONS: Sevoflurane depressed RV contractility to a lesser degree in PAH than in normal rats. Sevoflurane also upregulated iNOS expression and downregulated sGC expression in PAH, but not control rats. This observation may explain the differential effects of sevoflurane on RV function in rats with and without PAH. Abstract : Published ahead of print March 15, 2017.